The Influence of Marketing Innovation to Room Purchase Decision during Pandemic Covid-19 in Anantara Uluwatu Bali Resort - I Gusti Agung Gede Witarsana (Jurnal Pariwisata Terapan, 2022)
The Covid-19 pandemic has created unprecedented business changes and has significantly impacted the tourism sector. Hotels began to carry out adaptive capabilities and create improvements through innovative practices to maintain the company's viability by focusing on market changes and taking advantage of potential market share. In the light of this phenomenon, this study aims to determine the effect of marketing innovation on room purchasing decisions at Anantara Hotel Uluwatu Bali Resort. Data collection techniques used in this study were documentation, interviews, and questionnaires. Purposive sampling is used by taking responses of 50 people. In addition, this study used simple linear regression analysis techniques, t-test, and coefficient of determination (R2).Based on the simple linear regression analysis result produces the equation Y = 0.001 + 1.027 X. The t-test points out that the t-value of 13,870 is greater than the t-table of 1.98472. Similarly, the t-test results in the t-calculation of 11.888, which is greater than the t-table of 2.011. The coefficient of determination test produces an R2 value of 0.746, meaning that marketing innovation (X) affects 74.6% of the room purchase decision (Y). In comparison, the remaining 25.4% is explained by other variables not discussed in this study. Hence, result it is found that marketing innovation positively affects room purchasing decisions.